2007
DOI: 10.1073/pnas.0610552104
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Hurricanes Katrina and Rita on the microbial landscape of the New Orleans area

Abstract: Floodwaters in New Orleans from Hurricanes Katrina and Rita were observed to contain high levels of fecal indicator bacteria and microbial pathogens, generating concern about long-term impacts of these floodwaters on the sediment and water quality of the New Orleans area and Lake Pontchartrain. We show here that fecal indicator microbe concentrations in offshore waters from Lake Pontchartrain returned to prehurricane concentrations within 2 months of the flooding induced by these hurricanes. Vibrio and Legione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
82
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 35 publications
4
82
0
Order By: Relevance
“…DNA extraction was performed from the entire sterivex filter (see Sample collection section) using the Gentra Puregene Kit (Qiagen, Valencia, CA, USA) as described previously (Sinigalliano et al, 2007), in combination with a lytic enzyme solution (Qiagen; Zettler, 2013). DNA extracts were stored at − 80°C until PCR amplification.…”
Section: Methane Oxidation Ratesmentioning
confidence: 99%
“…DNA extraction was performed from the entire sterivex filter (see Sample collection section) using the Gentra Puregene Kit (Qiagen, Valencia, CA, USA) as described previously (Sinigalliano et al, 2007), in combination with a lytic enzyme solution (Qiagen; Zettler, 2013). DNA extracts were stored at − 80°C until PCR amplification.…”
Section: Methane Oxidation Ratesmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) amplification, cloning and sequencing Genomic DNA from each of the 27 samples was PCR amplified in triplicate using universal primers designed to target all three domains of life (bacteria, archaea and eukarya; Sinigalliano et al, 2007). This region spans E. coli positions 517-1391 corresponding to hypervariable regions V4-V8.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Clearly, the microbial burden of the floodwaters was very large. In contrast, after the floods had receded, Sinigalliano et al (5) rarely found Lake Pontchartrain water to exceed the aforementioned Environmental Protection Agency exposure level, and then only at stations near the shoreline. Water samples from the canals, however, frequently exceeded the mark.…”
Section: Fecal Contamination During and After The Floodsmentioning
confidence: 99%
“…What are the concerns associated with the sediment, toxic chemicals, metals, and microbes mobilized by the hurricanes? In a recent issue of PNAS, Sinigalliano et al (5) consider the poststorm ''microbial landscape'' of New Orleans and environs. They show that Lake Pontchartrain's microbial environment returned to prestorm (but not pristine) conditions 2 months after the hurricanes.…”
mentioning
confidence: 99%
See 1 more Smart Citation